1983
DOI: 10.1128/aac.23.3.390
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of herpes simplex virus DNA synthesis by pokeweed antiviral protein

Abstract: Pokeweed antiviral protein at a concentration of 3 FM inhibited both the synthesis and release of infectious herpes simplex virus type 1 in cell culture by 90 and 99%, respectively. Addition of pokeweed antiviral protein to Vero cell monolayers before virus infection was 10 to 15% more effective in reducing virus yields than was the simultaneous addition of the antiviral protein with virus inoculum. Viral DNA synthesis was inhibited by 90% in cells which had been exposed to the antiviral protein, whereas cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 20 publications
(19 reference statements)
0
24
0
Order By: Relevance
“…All of the biological properties of RIPs were attributed to the inactivation of ribosomes. However, some observations could not be equated with this view : (i) an effect of RIPs on viral DNA synthesis independent of the action of ribosomes was postulated by Teltow et al [8], who observed that pokeweed anti-viral protein (PAP) inhibits viral DNA synthesis to a much greater extent than cell protein synthesis in cells infected with the herpes simplex virus ; (ii) histological aspects of lesions induced by RIPs [9] are quite different from those obtained with other known protein synthesis inhibitors, and (iii) some aspects of the antiviral activity of RIPs could not be attributed to this property [10][11][12]. Furthermore, preliminary results showed that some saporins released adenine from all RNAs tested, and also from poly(A) and DNA, but did not affect ribomononucleotides, thus being actually polynucleotide :adenosine glycosidases [13].…”
Section: Introductionmentioning
confidence: 84%
“…All of the biological properties of RIPs were attributed to the inactivation of ribosomes. However, some observations could not be equated with this view : (i) an effect of RIPs on viral DNA synthesis independent of the action of ribosomes was postulated by Teltow et al [8], who observed that pokeweed anti-viral protein (PAP) inhibits viral DNA synthesis to a much greater extent than cell protein synthesis in cells infected with the herpes simplex virus ; (ii) histological aspects of lesions induced by RIPs [9] are quite different from those obtained with other known protein synthesis inhibitors, and (iii) some aspects of the antiviral activity of RIPs could not be attributed to this property [10][11][12]. Furthermore, preliminary results showed that some saporins released adenine from all RNAs tested, and also from poly(A) and DNA, but did not affect ribomononucleotides, thus being actually polynucleotide :adenosine glycosidases [13].…”
Section: Introductionmentioning
confidence: 84%
“…RIP Activity on pUC18 DNA-The amounts of protein and DNA are indicated in the figure legends. Reactions were carried out in 10 mM HEPES, pH 7.5, 0.1 mM ZnSO 4 , and the products were resolved by gel electrophoresis in 16 mM HEPES-KOH, 16 mM sodium acetate, 0.8 mM EDTA (18). For the inhibition study with NaBH 4 , a stock solution (1 M) was freshly prepared immediately prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…RIP Activity on ODNs-1 g of gelonin or PAP or 2 g of ricin, in 10 mM HEPES, pH 7, 0.1 mM ZnSO 4 , was incubated at 37°C for 1 h with the appropriate oligonucleotide in a reaction volume of 10 l at protein/ DNA molar ratios of 2:1. To assay for DNA glycosylase activity in the absence of spontaneous cleavage, a post-treatment with 10 mM spermidine for 30 min at 37°C was performed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations